Refining of atmospheric transport model entries by the globally observed passive tracer distributions of 85krypton and sulfur hexafluoride (SF6) - Levin, Ingeborg; Hesshaimer, Vago (1996)
Our high precision data base of the global distribution of SF6 in the troposphere [Maiss et al., 1996] is used in a two-dimensional atmospheric transport model (2D-HD model) to study the behaviour of this new tracer in comparison to the classical global atmospheric transport tracer 85Krypton. The 2D-HD model grid has been deduced from the 3D Hamburg TM2 model with the same resolution in the vertical and meridional direction, and was designed to run on any standard personal computer. The same vertical convection scheme and wind field as in the TM2 model, reduced to two dimensions, were used in the calculations. In addition, the horizontal diffusion parameter of the model was fine-tuned by matching the model estimated mean meridional 85Krypton distribution with observations over the Atlantic ocean. For simulating global tropospheric SF6 concentrations, an almost linearly increasing SF6 source strength was applied since 1970. The latitudinal distribution of the SF6 source was assumed to be similar to the global electrical power production. Excellent agreement between SF6 model results and observations is achieved with the 85Krypton-tuned 2D-HD transport model with respect to the global meridional concentration distribution and particularly in mid to high northern latitudes. In the southern hemisphere, at the German Antarctic Neumayer station, a significant seasonal cycle of SF6 has been observed which is reproduced by the model, however with a smaller ampitude. This finding may point to possible shortcomings of the model's transport scheme when simulating the seasonality of stratosphere-troposphere exchange in high southern latitudes.